\(\frac{2}{5}\)+\(\frac{5}{20}\) x 2 x \(\frac{13}{10}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(x+\frac{3+\frac{3}{20}+\frac{3}{13}+\frac{3}{2013}}{5+\frac{5}{20}+\frac{5}{13}+\frac{5}{2013}}=\frac{9}{2}\)
\(x+\frac{3\times\left(1+\frac{1}{20}+\frac{1}{13}+\frac{1}{2013}\right)}{5\times\left(1+\frac{1}{20}+\frac{1}{13}+\frac{1}{2013}\right)}=\frac{9}{2}\)
\(x+\frac{3}{5}=\frac{9}{2}\)
\(x=\frac{39}{10}\)
\(x=3,9\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Tìm x, biết:
3(x+2)(x+5) +5(x+5)(x+10) +7(x+10)(x+17) =x(x+2)(x+17) (x∉−2;−5;−10;−17)
2(x−1)(x−3) +5(x−3)(x−8) +12(x−8)(x−20) −1x−20 =−34 (x∉1;3;8;20)
x+110 +2+111 x+112 =x+113 +x+114
x−1030 +x−1443 +x−595 +x−1488 =0
![](https://rs.olm.vn/images/avt/0.png?1311)
3 + \(\frac{3}{20}\)+ \(\frac{3}{13}\) + \(\frac{3}{2013}\)
X x = \(\frac{5}{3}\)
5 + \(\frac{5}{20}\) + \(\frac{5}{13}\) + \(\frac{5}{2013}\)
3 x ( 1 + \(\frac{1}{20}\) + \(\frac{1}{13}\) + \(\frac{1}{2013}\) )
X x = \(\frac{5}{3}\)
5 x ( 1 + \(\frac{1}{20}\) +\(\frac{1}{13}\) + \(\frac{1}{2013}\) )
X x \(\frac{3}{5}\) = \(\frac{5}{3}\) => X = \(\frac{25}{9}\) vậy X = \(\frac{25}{9}\)
Ta có : \(X.\frac{3+\frac{3}{20}+\frac{3}{13}+\frac{3}{2013}}{5+\frac{5}{20}+\frac{5}{13}+\frac{5}{2013}}=\frac{5}{3}\)
\(\Leftrightarrow X.\frac{3\left(1+\frac{1}{20}+\frac{1}{13}+\frac{1}{2013}\right)}{5\left(1+\frac{1}{20}+\frac{1}{13}+\frac{1}{2013}\right)}=\frac{5}{3}\)
\(\Leftrightarrow X.\frac{3}{5}=\frac{5}{3}\Rightarrow X=\frac{5}{3}:\frac{3}{5}=\frac{5}{3}.\frac{5}{3}=\frac{25}{9}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
b)\(\frac{x-1}{x+5}=\frac{6}{7}\)
\(\Leftrightarrow7x-7=6x+30\)
\(\Leftrightarrow7x-6x=30+7\)
\(\Leftrightarrow x=37\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{13}{20}+\left(\frac{3}{5}+x\right)=\frac{5}{6}\)
\(\Rightarrow\frac{3}{5}+x=\frac{11}{60}\)
\(\Rightarrow x=-\frac{5}{12}\)
\(\frac{2}{5}+\frac{3}{5}:x=-3\)
\(\Rightarrow\frac{3}{5}:x=-\frac{17}{5}\)
\(\Rightarrow x=\frac{3}{5}:-\frac{17}{5}\)
\(\Rightarrow x=\frac{3}{-17}\)
~ nhé ! Mơn ạ ~
~ Học tốt ~
\(\frac{13}{20}+\left(\frac{3}{5}+x\right)=\frac{5}{6}\)
\(\frac{3}{5}+x=\frac{5}{6}-\frac{13}{20}\)
\(\frac{3}{5}+x=\frac{11}{60}\)
\(x=\frac{11}{60}-\frac{3}{5}\)
\(x=-\frac{5}{12}\)
\(\frac{2}{5}+\frac{3}{5} :x=-3\)
\(\frac{3}{5}:x=-3-\frac{2}{5}\)
\(\frac{3}{5}:x=-\frac{17}{5}\)
\(x=\frac{3}{5}:\left(-\frac{17}{5}\right)\)
\(x=-\frac{3}{17}\)
\(\frac{2}{5}\)+ \(\frac{5.13}{10.10}\)= \(\frac{2.20+65}{100}\)=\(\frac{105}{100}\)= \(\frac{21}{20}\)
2/5 + 5/20 x 2 x 13/10 = 21/20